APPLICATION OF INTERNET OF THINGS BASED ROOM SECURITY SYSTEM USING ANDROID APPLICATION - Rafif Muhammad Irdian; Rafi Fredy Septianto; Aksen Winarto (Jurnal Cakrawala Ilmiah, 2021)
Along with the increasing crime rate of data theft that occurs, it takes a good room security system to maintain data security for a particular agency or organization. Something A good security system is a security system that can be monitored and controlled remotely using the internet or better known as IoT (Internet of Things). In this thesis will designed an IoT-based room security system using the Android application, this system works using several modules including RFID (Radio Frequency Identification) module, camera module and door lock solenoid. The RFID card in this RFID Module functions as an identification process for people who want to enter into the room. In addition, this RFID module also functions as a trigger for the camera to work to take pictures a picture of the person who wants to enter the room. The data obtained from the two modules later will be sent into the Android application. The admin of the room can carry out the verification process to allow or deny people who want to enter the room. The results of testing this system can be runs well when the internet speed of the access point is fast and stable, but less optimal when the internet speed of the access point is running slowly.